Intravascular Imaging Guidance Reduce 1-Year MACE in Patients Undergoing Rotablator Atherectomy-Assisted Drug-Eluting Stent Implantation - Wongpraparut, Nattawut; Bakoh, Paroj; Anusonadisai, Kawin; Wongsawangkit, Namthip; Tresukosol, Damras; Chotinaiwattarakul, Chunhakasem; Phankingthongkum, Rewat; Tungsubutra, Wiwun; Chunhamaneewat, Narathip; Towashiraporn, Korakoth; Phichaphop, Asa; Panchavinnin, Pariya; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objectives: This study aimed to investigate the incidence of 1-year major adverse cardiac events (MACE) compared between intravascular imaging guidance and angiographic guidance in patients undergoing rotablator atherectomy (RA)-assisted percutaneous coronary intervention (PCI) with drug-eluting stent (DES) implantation. Methods: This retrospective analysis included 265 consecutive patients with heavy calcified lesion who underwent RA-assisted PCI with DES implantation at our institution during the January 2016-December 2018 study period. This study was approved by the Siriraj Institutional Review Board. Patients were divided into either the angiographic guidance PCI group or the imaging guidance PCI group, which was defined as intravascular ultrasound or optical coherence tomography. The primary endpoint was 1-year MACE. Results: Two hundred and sixty-five patients were enrolled, including 188 patients in the intravascular imaging guidance group, and 77 patients in the angiographic guidance group. One-year MACE was significantly lower in the imaging guidance group compared to the angiographic guidance group (4.3 vs. 28.9%, respectively; odds ratio (OR): 9.06, 95% CI: 3.82–21.52; p < 0.001). The 1-year rates of all-cause death (OR: 8.19, 95% CI: 2.15–31.18; p = 0.002), myocardial infarction (MI) (OR: 6.13, 95% CI: 2.05–18.3; p = 0.001), and target vessel revascularization (TVR) (OR: 3.67, 95% CI: 1.13–11.96; p = 0.031) were also significantly lower in the imaging guidance group compared with the angiographic guidance group. The rate of stroke was non-significantly different between groups. Conclusion: In patients with heavy calcified lesion undergoing RA-assisted DES implantation, the intravascular imaging guidance significantly reduced the incidence of 1-year MACE, all-cause death, MI, and TVR compared to the angiographic guidance.